Optimization of Terminal Facilities to Improve Service Quality to Service Users at Tjilik Riwut Airport, Palangkaraya, Central Kalimantan - Ripki Yuan Pratama; Eny Sri Haryati (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Palangka Raya Tjilik Riwut Airport is currently optimizing the terminal. This is done with the aim of improving the quality of services at Tjilik Riwut Palangka Raya Airport. The purpose of this research is to find out whether the terminal facilities at Tjilik Riwut Palangka Raya Airport are optimal or not. This research is a qualitative research using primary and secondary data. Primary data obtained from interviews and observation results. Secondary data is in the form of company documents and searches through literature. Data analysis techniques using data reduction analysis, data presentation, and drawing conclusions. The results of this study indicate that the terminal facilities at Tjilik Riwut Palangka Raya Airport are still lacking or can be said to be not optimal, such as the number of trolleys, directions in public areas, and smoking rooms. Facilities at Tjilik Riwut Palangka Raya Airport are quite good, but there are several facilities that need to be optimized again, such as toilet facilities, ATM centers, air conditioning in the waiting room, resulting in services that seem not optimal.